Models of living and non-living beings among indigenous community children - LETICIA GALLEGOS-CÁZARES; BEATRIZ GARCÍA-RIVERA; FERNANDO FLORES-CAMACHO; ELENA CALDERÓN-CANALES (Metaichmio Publications, 2016)
The aim of this paper is to understand the way indigenous Nahua children classify entities as living/non-living and justify their classification and to determine whether there is a biological thinking related to their particular cultural background. Thirty-three children from a public elementary school located in the Sierra Norte of Puebla were interviewed within and outside an academic context. From the analysis, we identified three main models: an intuitive model, a school biology model and a cultural model. The data suggest that the three models can coexist in children's explanations. The use of both the intuitive model and school biology model increase with education, but the cultural model is not abandoned.